Mutation scanning of BRAF, NRAS, KIT, and GNAQ/GNA11 in oral mucosal melanoma: a study of 57 cases. (24th September 2015) - Lyu, Jiong; Wu, Yunteng; Li, Chaojun; Wang, Runxiang; Song, Hao; Ren, Guoxin; Guo, Wei
Abstract : Background: Recent advances in novel targeted therapies have created the need for molecular characterization of cancer to allow accurate personalized treatments. In this study, our aim was to investigate the incidence of activating mutations of oncogenes BRAF, NRAS, KIT, and GNAQ / GNA11 in oral mucosal melanoma. Methods: We analyzed a cohort of 57 oral mucosal melanoma samples, including 27 frozen samples and 30 formalin‐fixed paraffin‐embedded samples. The tumors were screened for hotspot mutations of BRAF (exon 15), NRAS (exons 2 and 3), KIT (exons 9, 11, 13, and 17), and GNAQ/GNA11 (exon 5) by high‐resolution melting and direct sequencing. Results: In oral mucosal melanoma, 7.0% of tumors harbored KIT mutations and 3.5% harbored BRAF mutations, while classic BRAF V600E mutation was not detected. We found no mutations of NRAS or GNAQ / GNA11 in oral mucosal melanoma. Conclusion: We demonstrated that driver mutations are rare in mutational hotspots of BRAF, NRAS, KIT, and GNAQ / GNA11 in oral mucosal melanoma. The majority of patients will not benefit from KIT and BRAF inhibitors.